Research on the dynamic variation law of the discontinuous characteristics of the curvic coupling of aero-engine rotors under working conditions - Xing Heng; Ailun Wang; Haibiao Zhang; Yijun Yin (Engineering Science and Technology, an International Journal)
For the design of advanced aero-engine rotor systems under ultra-high rotational speeds, this paper undertakes a comprehensive investigation into the contact stiffness of curvic couplings, which are the key connection mechanism of modern aero-engine rotors, and explores the dynamic variations in the contact stiffness of curvic couplings under working conditions. Firstly, the impact of dynamic loads of aero-engine rotors under working conditions on the curvic coupling is studied; Then, the contact stiffness analytical model of curvic couplings considering three-dimensional geometric features is proposed with the effects of dynamic loads; Finally, based on the established stiffness model, the dynamic loss laws of contact stiffness of curvic couplings under different dynamic loads are investigated, and the established model is experimentally validated. The results show that the dynamic loss law of contact stiffness varies with different dynamic loads. In comparison to the contact stiffness under the static condition, dynamic loads significantly reduce the contact stiffness of curvic couplings under working conditions, which in turn leads to changes in the dynamic characteristics of the rotor with curvic couplings. For the safe integration of the discontinuous rotor system under ultra-high rotational speeds, it is essential to carefully design and regulate the operating speed, transmission torque, unbalanced mass, and preload.